Tourism Economics - Panasiuk, Aleksander (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The issues relating to the functioning of the tourism economy include both the activities of tourism enterprises and spatial units, i.e., tourism destinations, as well as tourism demand, including tourists' purchasing behavior. The aim of the Special Issue of Economies is to present the current results of research on the functioning of the tourism market and its individual elements. The presented studies refer to four groups of issues: the foundations of the tourism industry, including general rules and economic mechanisms related to the operation of this industry market; the functioning of tourism entrepreneurs, especially in the tourism industry, mainly in the area of accommodation offers; the operation of tourist destinations and the available offers in tourist areas; the trends in tourist demand, including the purchasing behavior of tourists in tourist destinations.